2) \( \frac{3 x}{5}+10=6 x-\frac{x+6}{3} \)
Solución de tutoría real
Responder
Solución
Revisado y aprobado por el equipo de tutoría de UpStudy
The Deep Dive
To solve the equation \( \frac{3 x}{5} + 10 = 6 x - \frac{x + 6}{3} \), start by getting rid of the fractions. You can do this by finding a common denominator, which in this case would be 15. Multiply everything by 15 to eliminate the denominators, resulting in \( 9x + 150 = 90x - 5(x + 6) \). Simplifying further, you'll get \( 9x + 150 = 90x - 5x - 30 \), which simplifies to \( 9x + 150 = 85x - 30 \). Rearranging gives \( 150 + 30 = 85x - 9x \) or \( 180 = 76x \), leading to \( x = \frac{180}{76} = \frac{45}{19} \). Now that you have your solution, remember to check your work by substituting \( x = \frac{45}{19} \) back into the original equation to ensure both sides are equal, which is always a good practice to confirm accuracy!